2020
DOI: 10.1177/0363546520924823
|View full text |Cite
|
Sign up to set email alerts
|

Graft-Preserving Arthroscopic Debridement With Hardware Removal Is Effective for Septic Arthritis After Anterior Cruciate Ligament Reconstruction: A Clinical, Arthrometric, and Magnetic Resonance Imaging Evaluation

Abstract: Background: Arthroscopic debridement with graft preservation has been advocated as the treatment of choice for septic arthritis after anterior cruciate ligament (ACL) reconstruction, but no previous studies have investigated if hardware removal, while retaining the graft in situ, improves the success rate. Moreover, it is unclear whether the premature removal of fixation devices may affect graft integration and knee stability. Purpose/Hypothesis: The purpose was to assess the clinical and functional outcomes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…This information strongly suggests the importance of the chondrolytic effect of SA after ACL reconstruction. Pogorzelski et al 17 and Lo Presti et al 10 reported MRI signs of chondral defect appearing in 69% and 63%, respectively, at final follow-up (103 and 101 months). However, as compared with our study design, their follow-up time was >2 times longer, and no control group was presented.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This information strongly suggests the importance of the chondrolytic effect of SA after ACL reconstruction. Pogorzelski et al 17 and Lo Presti et al 10 reported MRI signs of chondral defect appearing in 69% and 63%, respectively, at final follow-up (103 and 101 months). However, as compared with our study design, their follow-up time was >2 times longer, and no control group was presented.…”
Section: Discussionmentioning
confidence: 97%
“…Arthroscopic debridement with graft preservation and antibiotic therapy has been advocated as the treatment of choice. 10 There is no consensus about the best treatment modality, especially regarding hardware removal and graft-retaining protocol. 10 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Arthroscopic debridement shows obvious clinical results in elbow OA, and joint foreign body and impingement are considered potential indications (MacLean et al., 2013 ; Carlier et al., 2019 ; French Arthroscopic Society, 2019). Some studies showed that arthroscopic debridement and lavage are also effective in the improvement of symptoms in shoulder, knee and thumb OA (Furia, 2010 ; Bexkens et al., 2018 ; Lo Presti et al., 2020 ). However, some clinical trials and the systematic review showed unsatisfactory results for debridement and lavage procedures that the outcomes after surgery are temporary or no different from placebo procedures (Moseley et al., 2002 ; Kirkley et al., 2008 ; Skelley et al., 2015 ).…”
Section: Management Of Oamentioning
confidence: 99%
“…Delayed or missed treatment can lead to poor patient outcomes secondary to graft loss, chondral damage, secondary osteoarthritis, arthrofibrosis, and sepsis. [3][4][5] However, with early recognition, diagnosis, and aggressive management, infections can be treated successfully and the ACL graft retained. 1,2,[4][5][6] One must have a high level of suspicion and low threshold for evaluation for possible septic arthritis after ACL reconstruction.…”
Section: See Related Article On Page 1522mentioning
confidence: 99%